Country size and publicly provided goods - Klaas Staal (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
This paper studies the equilibrium size of countries. Individuals in small countries have greater influence over the nature of political decision making while individuals in large countries have the advantage of more public goods and lower tax rates. The model implies that (i) there exists excessive incentives to separate, though this need not be the case for all sets of secession rules studied; (ii) an exogenous increase in public spending decreases country size; (iii) countries with a presidential-congressional democracy are larger than countries with a parliamentary democracy.
urn:nbn:de:bvb:19-epub-13364-1
Keywords: D7; H1; H2; H7; 330; country size; public spending; structure of government